2001
DOI: 10.1136/ard.60.4.359
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for haematogenous bacterial arthritis in patients with joint disease: a cost effectiveness analysis

Abstract: Objective-To assess the cost eVectiveness of antibiotic prophylaxis for haematogenous bacterial arthritis in patients with joint disease. Methods-In a decision analysis, data from a prospective study on bacterial arthritis in 4907 patients with joint disease were combined with literature data to assess risks and benefits of antibiotic prophylaxis. EVectiveness and cost eVectiveness calculations were performed on antibiotic prophylaxis for various patient groups. Grouping was based on (a) type of event leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…Our data suggested no clear evidence between postoperative UTI and joint infection, which is consistent with the literature [22,24,36,41]. The majority of bacteria we observed were not enteric pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…Our data suggested no clear evidence between postoperative UTI and joint infection, which is consistent with the literature [22,24,36,41]. The majority of bacteria we observed were not enteric pathogens.…”
Section: Discussionsupporting
confidence: 91%
“…65 An analysis from The Netherlands concluded that for some patients with joint disease, but not with joint replacements, antibiotic prophylaxis before dental work was likely to be cost-effective. 85 In 1997, the American Dental Association and the American Academy of Orthopedic Surgeons issued an advisory statement 5,86 which was updated in 2003, together with the provision of an information leaflet for patients. 68 They stated that antibiotic prophylaxis is not mandatory for routine dental procedures in most patients with joint replacements, but should be considered in those with an increased risk, including joint replacement within the past two years, previous infection of a joint replacement, inflammatory arthritis, type-1 diabetes mellitus, haemophilia, immunosuppression, a history of previous or current malignancy, dental extractions, periodontal procedures, dental implantation, root canal work, descaling if bleeding was anticipated, specialised injections of local anaesthetic, or placement of orthodontic bands.…”
Section: Resultsmentioning
confidence: 99%
“…Second, infected foci elsewhere in the body 69 must be treated first. 5,6,8,13,20,24,33,66,80,84,85,94 Finally, all patients should be advised to establish and maintain good oral health.…”
Section: Nomentioning
confidence: 99%
“…The baseline scenario included direct healthcare costs in Spain, with inclusion of data drawn from the scientific literature (26), and Spanish drug directory (27). According to guidelines for economic evaluations, as well as commonly published cost‐effectiveness studies, cost‐effectiveness analysis should include direct costs, not only drug costs for maintenance treatment but also costs of associated contacts with healthcare professionals, such as doctors’ or nurses’ time, costs of the prescription and other intervention costs (28–34). Thus, the model included the costs of a 30‐minute outpatient visit to a general dentist for prescription of treatment and recommendations and of each of the drugs evaluated during the therapy period.…”
Section: Methodsmentioning
confidence: 99%